Effects of CRMP2 DNA Methylation in the Hippocampus on Depressive-Like Behaviors and Cytoskeletal Proteins in Rats - Xiang, Dan; Sun, Siqi; Wang, Gaohua; Liu, Zhongchun (Frontiers in Cellular Neuroscience, 2021)
Chronic stress appears to alter DNA methylation and DNA methyltransferases (DNMTs) in brain regions related to emotion. Collapsin response mediator protein-2 (CRMP2) mediates the development of depression by regulating microtubule dynamics. In this study, rats were subjected to chronic unpredictable mild stress (CUMS). At the end of the CUMS procedure, normal saline or fluoxetine was administered to the rats. Moreover, normal saline or the 5-aza-2’-deoxycytidine (5-aza) was administered to the hippocampal CA1 region of the rats. Behavioral tests were performed to evaluate the depressive-like phenotypes. The CRMP2 DNA methylation levels and cytoskeletal microtubular system-related biomarkers were detected by several molecular biology techniques. The results showed that the rat model of depression was successfully established by exposure to CUMS, and fluoxetine treatment exerted an antidepressant-like effect. We observed upregulation of DNMT1 and DNMT3a in the hippocampus of stressed rats. CUMS induced a decrease in CRMP2 expression and an increase in phosphorylated CRMP2 (pCRMP2) expression in the hippocampus of rats. The rate of DNA methylation in the CpG island of CRMP2 promoter region in the hippocampus of stressed rats was significantly higher than that in control rats. Moreover, CUMS significantly decreased the interaction between CRMP2 and α-tubulin and decreased the microtubule dynamics. Chronic fluoxetine treatment reversed these changes. In addition, hypomethylation induced by 5-aza injection into the hippocampal CA1 region caused antidepressant-like effects and increased CRMP2 expression and microtubule dynamics. These results suggested that CRMP2 DNA methylation may be involved in regulating the cytoskeletal microtubular system and mediating depressive-like behaviors.